Relationship between depth of soil moisture assessment and turgidity of coffee plant in selected agroclimates - Rudy Erwiyono; Aris Wibawa (JOURNAL OF TROPICAL SOILS, 2008)
Observation on the relationship between the depth of soil moisture assessment and turgidity of coffee plant has been carried out at 3 different agroclimates by survey method, i.e. Andungsari experimental station (Andosol soil type, >1.000 m asl. high, and rainfall type of C), Sumberasin experimental station (yellowish-red Mediterranean soil type, 450-500 m asl. high, and rainfall type of C, and Kaliwining experimental station (low humic glei soil type, 45 m asl. high, and rainfall type of D) in order to assess the depth of soil moisture through soil profile influencing turgidity of coffee plants at three different agroclimates.    The method of assessment is by fitting the relationship between the depth of soil moisture assessment and turgidity of coffee plant and their determination coefficients through the period of dry season up to early rainy season.   Plant turgidity is evaluated from its relative water contents of the leaves sampled periodically at the same time as observation of soil moisture content.  Plant turgidity is affected by soil moisture condition up to a certain depth which looks to be typical of the agroclimates.  At Andungsari experimental station (high land) it is necessary to assess soil moisture through the soil profile up to 100 cm deep in order to evaluate water stress of the plants; inversely, at Kaliwining experimental station in order to evaluate water stress of the plants it is just justified from the soil moisture condition of the soil surface layers (0-25 cm).  Whereas at Sumberasin experimental station water stress of the plants could be predicted from soil moisture assessment of the surface layer depth or through the deeper layers of the soil profile either.  Andungsari-1 and Lini S-795 clones are more resistant to drought than Kartika-2 clone at Andisol soil type with C rainfall type and elevation > 1000 m asl.   BP-308 clone showed its response as relatively resistant to drought at yellowish red Mediterranean soil type with C rainfall type at elevation around 500 m asl.   Robusta coffee clone with no name at Kaliwining experimental station showed wilting sign, reduction of its turgidity, and falling leaves during the dry season, and positively responding to soil moisture increase.   An effort to maintain plant turgidity with increasing soil water stress could be done by managing atmospheric demand to be lower.  Practical implications of the findings might be discussed a bit more deeply in this paper.